2001
DOI: 10.1007/s004280000295
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of events in the glomerular capillary wall at the onset of proteinuria in passive Heymann nephritis

Abstract: Proteinuria in passive Heymann nephritis (PHN) results from complement-mediated glomerular injury, since complement depletion with cobra venom factor (CVF) prevents proteinuria. However, there are no comprehensive morphological studies identifying the sites of injury leading to onset of proteinuria. To address this issue, we attempted to locate sites of injury involved in the onset of proteinuria in PHN. PHN was induced in intact Munich-Wistar rats (PHN-rats, examined at days 3, 5, and 7) and in complement-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…3). These findings are compatible with previous reports [13,14,42]. We also analyzed the staining of podocin and CD2AP as well as nephrin in passive Heymann nephritis rabbit.…”
Section: Fig 8 Western Blot Analyses Of the Sequentially Solubilizesupporting
confidence: 92%
See 2 more Smart Citations
“…3). These findings are compatible with previous reports [13,14,42]. We also analyzed the staining of podocin and CD2AP as well as nephrin in passive Heymann nephritis rabbit.…”
Section: Fig 8 Western Blot Analyses Of the Sequentially Solubilizesupporting
confidence: 92%
“…Twenty-four-hour urine samples were collected just before (day 0) and on days 3,5,7,11,14,21,28,35, and 42 after anti-Fx1A antibody injection. The amount of urinary protein excretion was measured by the Bradford method (Bio-Rad, Oakland, CA, USA).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that PHN is thought to have heterologous and autologous immune phases [35]. As far as two phases of PHN were concerned, the pathologic changes including proteinuria were mainly seen in the autologous immune phase [8].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of glomerular anionic sites has been documented in PHN using various cationic probes [1,[21][22][23] . In the study by Arai et al [21] , anionic charge of the GBM in the heterologous phase of PHN was examined by measurements of ruthenium red binding to the GBM.…”
Section: Discussionmentioning
confidence: 99%